2022
DOI: 10.1097/jpn.0000000000000617
|View full text |Cite
|
Sign up to set email alerts
|

Early Perinatal Workforce Adaptations to the COVID-19 Pandemic

Abstract: The objective of this study was to describe the system's initial pandemic response from the perspectives of perinatal health workers and to identify opportunities for improved future preparedness. An exploratory survey was designed to identify perinatal practice changes and workforce challenges during the initial weeks of the COVID-19 pandemic. The survey included baseline data collection and weekly surveys. A total of 181 nurses, midwives, and physicians completed the baseline survey; 84% completed at least 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Findings also show the positive role of community midwives in supporting birthing women during the pandemic and their ability to find innovative ways to offer care in the pandemic situation. Flexibility and their ability to work when supplies or institutional support is limited were particularly useful during this period [ 13 , 16 , 19 , 26 , 27 , 29 , 31 , 33 35 ]. Changes reported in their practices included more wearing of personal protective equipment (masks and gloves); sanitizing their workspace; fewer in-persons visits or childbirth classes; more video calls, phone calls, and virtual prenatal and post-partum visits; and sharing online documents to inform women [ 26 , 27 , 31 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Findings also show the positive role of community midwives in supporting birthing women during the pandemic and their ability to find innovative ways to offer care in the pandemic situation. Flexibility and their ability to work when supplies or institutional support is limited were particularly useful during this period [ 13 , 16 , 19 , 26 , 27 , 29 , 31 , 33 35 ]. Changes reported in their practices included more wearing of personal protective equipment (masks and gloves); sanitizing their workspace; fewer in-persons visits or childbirth classes; more video calls, phone calls, and virtual prenatal and post-partum visits; and sharing online documents to inform women [ 26 , 27 , 31 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, midwives and other birth workers are included as part of an all‐hands‐on‐deck approach that considers the role community settings may have in rationing hospital resources 47 . Implementing this guidance during the current pandemic and future disasters could allow perinatal health care systems to flex more efficiently to balance patient needs with risks of transmission and/or resource rationing 48 …”
Section: Discussionmentioning
confidence: 99%
“…A survey of people giving birth during the pandemic indicated that high‐quality perinatal care, defined by patient ratings of perceived autonomy and respectful care, was more likely for those giving birth in community settings or with midwives and less likely for people identifying as Black, as Indigenous, and as people of color and for those giving birth in hospitals or with physician care 35 . However, a national survey of perinatal care providers indicated that most midwives providing community care declined some patient transfers from hospital‐based care during the COVID‐19 pandemic because of patient inability to pay 48 . Thus, the pandemic effects of policies restricting licensure, reimbursement, and autonomy of qualified midwives compounded the harm to communities already suffering the consequences of a system plagued by structural racism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations